MEDIA POLICIES OF THE STATE IN THE TIME OF COVID-19 - Acharya, Anogh; Krishnan K., Unni (International Journal of Research -GRANTHAALAYAH, 2021)
Media and communication management during pandemic is very crucial to development process of the nation. This paper analyses four (public) policy level actions of India, through its media units and ministries viz., MIB, MoC and MeitY . It uses a self-curated analytical framework, under three themes to study the policies and discusses their relevance and effectiveness. From C-DOT’s launch of communication strategies, to facilitating smooth operations of media, to curbing misinformation on Corona virus and representing “positive news”, an in-depth analysis has been conducted based on the designed framework.